Effects of Social Media on People’s Tendency Toward Aesthetic Dental Treatments - Madihi, Saeed; Ghorbani, Zahra; Farrokhi, Farzaneh; Hasani, Ahmad (Journal of Dental School, 2023)
Objectives This study aimed to investigate the impact of social media on people’s tendency toward aesthetic dental treatments in Iran. Methods This cross-sectional study was performed on 410 individuals, including dentists or dental students and laypeople, who were selected via convenience sampling. A questionnaire, consisting of sociodemographic characteristics, frequency of social media use, tendency toward aesthetic dental treatments, and factors affecting people’s decisions, was completed for data collection. This online questionnaire was created using the Porsline© website and posted on social media. The collected data were analyzed in SPSS version 21, using Chi-square test. A P-value less than 0.05 was considered statistically significant. Results Of 410 participants, 157 (38.3%) were dentists or dental students. Only 38.2% of the participants in the dentist group were willing to receive aesthetic dental treatments, whereas laypeople were significantly more inclined to receive such treatments (69.2%) (P<0.001). Almost half of people who used social media platforms several times a day and also 71.8% of people who used social media once a day or less showed tendency toward aesthetic dental treatments (P=0.01). Conclusion Based on the results, the time spent on social media was not significantly associated with people's tendency to receive aesthetic dental treatments. Also, dentists were less interested in such treatments for themselves.